Planthopper-Secreted Salivary Disulfide Isomerase Activates Immune Responses in Plants - Fu, Jianmei; Shi, Yu; Wang, Lu; Zhang, Hao; Li, Jing; Fang, Jichao; Ji, Rui (Frontiers in Plant Science, 2021)
The small brown planthopper (Laodelphax striatellus, SBPH) is a piercing-sucking insect that secretes salivary proteins into its host plants during the feeding. However, the mechanisms by which these salivary proteins regulate plant defense responses are poorly understood. Here, we identified a typical disulfide isomerase gene (LsPDI1) from SBPH salivary proteome. LsPDI1 was highly expressed in SBPH salivary glands and secreted into host rice plants during SBPH feeding. Transient LsPDI1 expression in planta, without signal peptide, induced a strong reactive oxygen species (ROS) burst, cell death, callose deposition, and the expression of defense-related genes associated with jasmonic acid signaling pathway. A deletion mutant analysis revealed that either a-b-b’ or b-b’-a’ domains in LsPDI1 are required to induce cell death in plants. LsPDI1 and its orthologs are highly conserved among various planthopper species and strongly induce cell death in plants. Most importantly, transient LsPDI1 expression in planta impaired the performance of Spodoptera frugiperda or Myzus persicae on host plants. Hence, LsPDI1 is an important salivary elicitor that enhances plant resistance to insects by eliciting the ROS, calcium and jasmonic acid signaling pathways. These findings provide novel insights into molecular mechanisms underlying plant-insect interactions.